Valorization of Mussel Shell Waste to Chitin, Chitosan, and Calcium Lactate for Bio-Green-Circular Management - Seangarun, Chaowared; Seesanong, Somkiat; Boonchom, Banjong; Boonmee, Wimonmat; Punthipayanon, Sirichet; Laohavisuti, Nongnuch; Rungrojchaipon, Pesak (My University, 2026)
This study presents a green bio-upcycling strategy for converting mussel shell biowaste into three value-added products: chitin, chitosan, and calcium lactate. Mussel shells were treated chemically with lactic acid during demineralization, yielding a solid fraction rich in chitin and a liquid fraction containing calcium and lactate ions. The solid fraction was sequentially purified by deproteinization and decolorization, then deacetylated to obtain chitosan, while the liquid fraction was evaporated to obtain calcium lactate. Notably, 2.37 g of raw chitin, 2.15 g of purified chitin, and 275.87 g of calcium lactate were obtained from 100 g of mussel shells, demonstrating the efficiency of the process. FTIR spectra revealed characteristic absorption bands corresponding to α-chitin and chitosan functional groups, while XRD patterns indicated the crystalline α-chitin structure and the formation of calcium lactate pentahydrate. TGA demonstrated the high thermal stability of chitin and chitosan and confirmed the presence of crystallization water in calcium lactate. In conclusion, these results confirmed the successful preparation of α-chitin, chitosan, and calcium lactate pentahydrate, with improved purity compared to previous studies. This approach highlights the potential of the green bio-upcycling process of mussel shell waste as a renewable source for the eco-friendly production of biopolymers and calcium salts, supporting sustainable waste management and the development of the Bio-Circular-Green (BCG) economy.
Keywords: calcium lactate; chitin; chitosan; mussel shell waste; sustainable waste management; upcycling